Perencanaan Jembatan Kayu di Jalan Pertanian Desa Mekar Sari Kecamatan Benua Kayong Kabupaten Ketapang - Suryansyah, Suryansyah; Purnomo, Julyan; Kamil, Firmanilah (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2022)
On Agricultural Road Mekar Sari Village, Benua Kayong District, Ketapang Regency, West Kalimantan there are still roads that are separated by the flow of the river where the roads can be used by farmers in bringing their agricultural products to their destination, therefore the construction of bridges must be carried out at that location. At this time the planner used a type of concrete floor wooden bridge that was in accordance with the needs in the field. The objectives to be achieved are to make a plan drawing and calculate the budget required for the construction of a bridge on Road Agriculture. To obtain the data in this study, researchers used field observations and data collection for the 2021 Ketapang Regency material unit price list from PUPR to make the RAB. After making the plan drawings and analyzing the RAB calculation, the total cost needed for the construction of the bridge on Road Agriculture, Mekar Sari Village, is Rp. 31.357.000